MEDIA LOOSE PART PLAY DALAM MERANSANG PERKEMBANGAN KOGNITIF ANAK USIA DINI - Ulfa Tia Ramlah; Arifah A Riyanto; Lenny Nuraeni (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2022)
Giving stimulation to early childhood is very important for the growth of the relationship between brain nerve cells by stimulating aspects of their development. Aspects of development that must be developed are aspects of cognitive development. Developments that are included in the cognitive aspect are the development of problem solving, logical thinking and exploring objects to stimulate children's cognitive development using the loose parts play media. The media used by these students can be transferred, transported, put together, changed in various forms according to their own wishes, namely games using Loose Parts Play media. The media can be used independently or mixed with other materials. With their imagination using these media Children can build or design an activity with these materials. The purpose of writing this article is to describe the achievement of AUD cognitive development which is stimulated through Loose Parts Play media. Descriptive qualitative is the method that will be used in this research. Observation, interview and documentation are data collection techniques used and data analysis used is narrative. The subjects in this study were children of group B Paud Nurul Ilmi Bandung. The result is the achievement of children's cognitive development looks well developed. Thus, the conclusion of this study is about the achievement of cognitive development of early childhood children Nurul Ilmi Bandung.Pemberian rangsangan pada Anak Usia Dini sangat penting untuk pertumbuhan hubungan antar sel syaraf otak dengan menstimulus aspek perkembangannya. Aspek perkembangan yang harus dikembangkan yaitu aspek perkembangan kognitif. Perkembangan yang termasuk dalam aspek kognitif adalah perkembangan memecahkan masalah, berpikir logis dan mengeksplorasi benda untuk meransang perkembangan kognitif anak menggunakan media loose parts play tersebut. Media yang dipakai oleh peserta didik tersebut bisa dialihkan, diangkut, disatukan, diubah dengan berbagai macam bentuk sesuai keinginannya sendiri yaitu permainan menggunakan media Loose Parts Play. Media tersebut bisa dipergunakan secara mandiri ataupun dicampurkan dengan bahan lain. Dengan imajinasi mereka menggunakan media tersebut Anak Anak dapat membangun atau merancang suatu kegiatan dengan bahan-bahan tersebut. Tujuan penulisan artikel ini adalah untuk mendeskripsikan tentang pencapaian perkembangan kognitif AUD yang diransang melalui media Loose Parts Play. Kualitatif deskriptif adalah metode yang akan digunakan dalam penelitian ini. Observasi, wawancara dan dokumentasi adalah teknik pengumpulan data yang digunakan dan analisis data yang digunakan adalah naratif. Subjek pada penelitian ini adalah anak kelompok B Paud Nurul Ilmi Bandung. Hasilnya adalah pencapaian perkembangan kognitif anak terlihat berkembang dengan baik. Dengan demikian kesimpulan dari penelitian ini adalah mengenai pencapaian perkembangan kognitif anak Paud Nurul ilmi Bandung.